Dagmar Parer, 24 February 1948 – 4 November 2014 - Stephen Ellis; Adrian Cunningham (Archives & Manuscripts, 2015)
Members of the archives profession will have been saddened to hear of the loss of Dagmar Parer from our number late last year from mesothelioma. Dagmar made significant contributions to the work of archives, libraries and information services during a career spanning several decades across various locations in Australia.